KETERAMPILAN WIRAUSAHA UNTUK KEBERHASILAN USAHA - Aji, Sunan Purwa; Mulyadi, Hari; Widjajanta, Bambang (Business Education Program of Universitas Pendidikan Indonesia, 2018)
Objective - to know the description of entrepreneurial skills to business success.The design / methodology / approach - this study was conducted over a period of less than one year, the research design used was cross sectional method. This research uses verifikatif approach with explanatory survey method. A total of 34 respondents as samples using saturated samples. Questionnaire research is used as a research instrument to collect data from respondents and data analysis techniques used are simple linear regression.Findings - Entrepreneurial skills have a significant effect on business success.Originality - differences are found in independent variables, research objects and methods, population and sample research, research periods, measurement tools and research results, as well as sources of foreign theories and journals and books.